Maksim Gorki – dramatik ruske revolucije na slovenskih odrih - Troha, Gašper (Slavistična revija, 2025)
The article analyses the reception of Maxim Gorky’s plays The Lower Depths and Children of the Sun. Through a close reading of both plays and an analysis of critical responses to their performances, it charts the development of reception, which ranged from enthusiastic acceptance to a realisation of the irrelevance of the plays.
Keywords: Babič, Jože; dramatika realizma-naturalizma; Gorki, Maksim; naturalism; naturalizem; realism; realism-naturalism drama; realizem; recepcija; reception; ruska dramatika; ruska književnost; Russian drama; Russian literature; Slovene theatre; slovensko gledališče; socialist realism; socialistični realizem